ChemInform Abstract: Phenylthiocarbamate or N‐Carbothiophenyl Group Chemistry in Peptide Synthesis and Bioconjugation. Issue 22 (3rd June 2014) - Melnyk, Oleg; Ollivier, Nathalie; Besret, Soizic; Melnyk, Patricia
Abstract Review: 104 refs.